A national examination of discrimination, resilience, and depressive symptoms during the COVID-19 pandemic: the All of Us Research Program - Cook, Stephanie H.; Wood, Erica P.; Risner, Emma; Weng, Chenziheng Allen; Xin, Yao (Frontiers in Psychology, 2023)
Objective To examine the impact of resilience on the association between discrimination and trajectories of depressive symptoms during the COVID-19 pandemic across racial and ethnic groups. Methods Data were drawn from 5 waves of the All of Us Research Program’s survey on the impact of COVID-19 on the lives of American adults. Linear mixed-effects models were fitted to assess the association between discrimination exposure throughout the pandemic and depressive symptoms over time. An interaction term was introduced between resilience and discrimination exposure to assess if resilience buffered the association between discrimination and depressive symptoms over time. Race-stratified linear mixed-effects models examined racial/ethnic differences in the association between resilience, discrimination, and depressive symptoms over time. Results Fifty-one thousand nine hundred fifty-eight participants completed surveys between May and December of 2020. Results indicated that exposure to more discrimination was associated with increasing trajectories of depressive symptoms over time (b = 0.48, p < 0.001). However, resilience moderated the association between discrimination and well-being over time such that higher resilience mitigated the detrimental effect of experiencing discrimination on depressive symptoms across time (b = −0.02, p < 0.001). Conclusion Identifying protective features such as resilience can promote the development of culturally tailored interventions to address mental health in the context of discrimination.